Synthesis and Biological Evaluation of New Pyridothienopyrimidine Derivatives as Antibacterial Agents and Escherichia coli Topoisomerase II Inhibitors - Eman M. Mohi El-Deen; Eman A. Abd El-Meguid; Eman A. Karam; Eman S. Nossier; Marwa F. Ahmed (MDPI AG, 2020)
The growing resistance of bacteria to many antibiotics that have been in use for several decades has generated the need to discover new antibacterial agents with structural features qualifying them to overcome the resistance mechanisms. Thus, novel pyridothienopyrimidine derivatives (2a,b-a,b) were synthesized by a series of various reactions, starting with 3-aminothieno[2,3-b]pyridine-2-carboxamides (1a,b). Condensation of compounds 1a,b with cyclohexanone gave 1'H-spiro[cyclohexane-1,2'-pyrido[3',2':4,5]thieno[3,2-d]pyrimidin]-4'(3'H)-ones (2a,b), which in turn were utilized to afford the target 4-substituted derivatives (3a,b-8a,b). In vitro antibacterial activity evaluations of all the new compounds (2a,b-8a,b) were performed against six strains of Gram-negative and Gram-positive bacteria. The target compounds showed significant antibacterial activity, especially against Gram-negative strains. Moreover, the compounds (2a,b; 3a,b; 4a,b; and 5a,b) that exhibited potent activity against Escherichia coli were selected to screen their inhibitory activity against Escherichia coli topoisomerase II (DNA gyrase and topoisomerase IV) enzymes. Compounds 4a and 4b showed potent dual inhibition of the two enzymes with IC50 values of 3.44 µΜ and 5.77 µΜ against DNA gyrase and 14.46 µΜ and 14.89 µΜ against topoisomerase IV, respectively. In addition, docking studies were carried out to give insight into the binding mode of the tested compounds within the E. coli DNA gyrase B active site compared with novobiocin.